Reforms, Organizational Change and Performance in Higher Education A Comparative Account from the Nordic Countries - Pinheiro, Rómulo; Geschwind, Lars; Foss Hansen, Hanne; Pulkkinen, Kirsi (Springer Nature, 2019)
This open access book investigates the effects of changes in leadership and managerial structures of Nordic universities resulting from reforms in the last decade. It builds on a rich, comparative dataset across a multiplicity of system-wide (macro) and organisational (meso and micro) dimensions, namely: reform or policy initiatives; drivers, aims, instruments and actors; structural changes within universities; strategic and performance management; the rise of accountability regimes; incentive and evaluative systems; and perceived changes/effects by the key actors involved, at various levels. The volume provides critical insights to the larger phenomenon of change and adaptation within the public sector. Its findings and implications are of relevance to social science researchers, policy makers, managers/administrators, and external stakeholders.